Social Development and Gender Gap in Information Technology Perspective - Luluk Fauziah; Ni Luh Yulyana Dewi; Hefri Yodiansyah; Nani; Yohanes Bastian Vestralen Lameng (GoAcademica Research & Publishing, 2023)
ICT's rapid growth should benefit society. ICT can empower the poor, grow the economy, and develop society. However, ICT infrastructure growth is still not able to reach all levels of society, and its use might produce gender disparities in accessing social networks and social capital, especially for women. Women are still underrepresented in IT development. Skills, education, language barriers, time restrictions, sexy stereotypes that make women easy targets for harassment, and changing cultural and social standards all contribute to the digital divide of women. Information and communication technology is used to study social progress and gender gap (ICT). This study uses qualitative descriptive methodologies. This study revealed that social development based on ICT could be the key to economic growth and empowering the marginalized. Still, social development with ICT can create a gap that we know as the digital divide. The development of this digital divide is not only caused by the absence of tools but more than that due to a gender gap.